Computational empowerment: participatory design in education. Issue 1 (2nd January 2020) - Dindler, Christian; Smith, Rachel; Iversen, Ole Sejer
ABSTRACT: We propose computational empowerment as an approach and a Participatory Design (PD) response to challenges related to the emerging need for digital literacy in lower secondary education. Our approach extends the current focus on computational thinking to include a concern for how children and youth are empowered through constructive, analytical and critical engagement with technology. We argue that PD has the potential to drive a computational empowerment agenda in education by connecting political PD with contemporary visions for addressing a future digitised labour market and society. We provide a model for understanding and engaging with computational empowerment and report on the emergence of the computational empowerment agenda in a Danish context and how this agenda is reflected in the newly developed curriculum for a course on technology comprehension running on trial basis in 46 schools across Denmark.